2014
DOI: 10.1371/journal.pone.0086958
|View full text |Cite
|
Sign up to set email alerts
|

Young Children Understand the Normative Implications of Future-Directed Speech Acts

Abstract: Much recent research has shown that the capacity for mental time travel and temporal reasoning emerges during the preschool years. Nothing is known so far, however, about young children's grasp of the normative dimension of future-directed thought and speech. The present study is the first to show that children from age 4 understand the normative outreach of such future-directed speech acts: subjects at time 1 witnessed a speaker make future-directed speech acts about/towards an actor A, either in imperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Specifically, 5‐year‐olds distinguished between speakers that promised and helped and those who only helped, indicating that, under some conditions, children take both the promise speech act and the action into account. In line with other recent work (Lohse, Gräfenhain, Behne, & Rakoczy, ; Rakoczy & Tomasello, ), we show that a more sophisticated understanding of speech acts emerges already in the (late) preschool years and thus earlier than previously claimed (Astington, 1988a, 1988b; Rotenberg, ).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, 5‐year‐olds distinguished between speakers that promised and helped and those who only helped, indicating that, under some conditions, children take both the promise speech act and the action into account. In line with other recent work (Lohse, Gräfenhain, Behne, & Rakoczy, ; Rakoczy & Tomasello, ), we show that a more sophisticated understanding of speech acts emerges already in the (late) preschool years and thus earlier than previously claimed (Astington, 1988a, 1988b; Rotenberg, ).…”
Section: Discussionsupporting
confidence: 93%
“…Yet, a series of related studies has shown that preschoolers direct their protest at actors for failing to follow a directive (e.g., ''Put the red thing there!") and at speakers for failing to make accurate predictions or assertions (e.g., ''The red thing is/will be there") (Lohse, Gräfenhain, Behne, & Rakoczy, 2014;Rakoczy & Tomasello, 2009). Taken together, this indicates that young children may have a more nuanced understanding of speech acts and speakers' responsibility than was previously assumed.…”
Section: Resultsmentioning
confidence: 84%
“…Various research based on the class interaction shows the type of directive act of speech act variation, which usually used in interaction as well as in university level. These are showed in some research findings of directive speech act conducted by Shvartzman (2015), Field (2001), Beck (2008), Lohse (2014), George (2014), Arani (2012), Welvi (2015) Muhartoyo andKristian (2013), andPrayitno (2009).…”
Section: Introductionmentioning
confidence: 77%
“…It is also found by Lohse (2014) that the directive speech acts about/ towards an actor A. Either in imperative mode (A do X) or as a prediction (the actor A will do X).…”
Section: Resultsmentioning
confidence: 99%